1989
DOI: 10.1161/01.cir.79.3.634
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic assessment of regional cardiac adrenergic innervation.

Abstract: To assess the feasibility of noninvasively imaging the regional distribution of myocardial sympathetic innervation, we evaluated the distribution of sympathetic nerve endings, using 123I metaiodobenzylguanidine (MIBG), and compared this with the distribution of myocardial perfusion, using 201Tl. Twenty dogs were studied: 11 after regional denervation, and nine as controls. Regional denervation was done by left stellate ganglion removal, right stellate ganglion removal, and application of phenol to the epicardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 13 publications
3
65
0
4
Order By: Relevance
“…The available literature strongly supports that assumption. Phenol application to the epicardial surface has been employed for selective cardiac sympathetic afferent (5,34,37) and efferent (11,28,35) denervation based on anatomic observations (5) that the cardiac sympathetic afferent fibers course more superficially over the epicardial surface of the heart, whereas vagal afferent fibers run deeper until they reach the epicardial surface in the region of the atrioventricular groove. Most of these studies (5,34,35,37) have been performed in acute preparations like the present one.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature strongly supports that assumption. Phenol application to the epicardial surface has been employed for selective cardiac sympathetic afferent (5,34,37) and efferent (11,28,35) denervation based on anatomic observations (5) that the cardiac sympathetic afferent fibers course more superficially over the epicardial surface of the heart, whereas vagal afferent fibers run deeper until they reach the epicardial surface in the region of the atrioventricular groove. Most of these studies (5,34,35,37) have been performed in acute preparations like the present one.…”
Section: Discussionmentioning
confidence: 99%
“…13 Scintigraphic imaging in each of the phenol-treated rabbits demonstrated a heterogeneous distribution of MIBG uptake (innervation) and a homogeneous distribution of MIBI uptake (perfusion). Previous studies of MIBG uptake in the phenol model have shown that the reduction in uptake is due to an absence of sympathetic nerve terminals, or denervation.…”
Section: Scintigraphic Imaging Of Sympathetic Innervationmentioning
confidence: 93%
“…The 2 autoradiographs were compared on a pixel-by-pixel basis by a color method described previously. 13 Color slices were then aligned to create a set of 3D reconstructions of the heart.…”
Section: Computer Processing Of Autoradiographsmentioning
confidence: 99%
“…Ther e has been long-standing interest in noninvasive imaging of myocardial sympathetic innervation for the prediction of life-threatening ventricular arrhythmias or implantable cardioverter defibrillator discharges using PET (1)(2)(3)(4)(5) or SPECT (6)(7)(8). It has been shown (9)(10)(11) that, in myocardial infarction, the area of reduced innervation often exceeds the area of reduced myocardial blood flow (MBF) (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%